A STUDY OF MOORTHY'S TRANSFORMATION IN THE LIGHT OF GANDHIAN VALUES - Tiwari, Iti; Mudgal, Abhay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The novel's protagonist, Moorthy, exemplifies Gandhi's teachings on the value of truth and nonviolence in obtaining liberation. Moorthy represents Gandhi and brings together the villagers in their desire for independence. The narrative compares the independence movement to the principles of the Bhagavad Gita, with Moorthy promoting nonviolence and integrity among his fellow peasants. The story incorporates Gandhian traditions such as communal prayers, Harikatha recitation, and Khadi attire to reflect the community's values. This paper examines how Gandhi's principles influenced Raja Rao's portrayal of the character Moorthy in his novel. Gandhian beliefs influenced Moorthy's efforts to inspire others to join the Freedom Struggle. Raja Rao sees Gandhi as a guiding light, while Moorthy considers Gandhi's doctrine a guiding principle in life. This paper examines how Gandhi's principles influenced Raja Rao's portrayal of the character Moorthy in his novel. Gandhian beliefs influenced Moorthy's efforts to inspire others to join the Freedom Struggle. Raja Rao sees Gandhi as a guiding light, while Moorthy considers Gandhi's doctrine a guiding principle in life.